On the problem of legal protection of personal data (Journal of actual problems of jurisprudence, 2018)
The article analyzes the concepts and different regulatory approaches to the concept and content of personal citizens. The attention is focused on problems of the modern legislation on the status of personal information and their subjects. The examples from practice confirming existence of serious problems in the sphere of protection of personal information are given. Suggestions for improvement of the domestic legislation are made.Key words: personal data, privacy, information rights, confidentiality of information, personal data.